Діалектна фраземіка у "Словарі української мови" Б. Грінченка - Коваленко, Н.Д. (Лексикографічний бюлетень, 2013)
«Словарь української мови», співукладачем, упорядником і редактором якого був Б. Грінченко, – визначна лексикографічна праця, до якої долучили ся фольклористи, етнографи, письменники, мовознавці того часу. Науковці високо оцінили «Словарь…» за обсягом лексичного та фразеологічного ма теріалу, використанням джерел до ілюстративного матеріалу, точністю до‑ кументації та опису семантики мовних одиниць. «Vocabulary of Ukrainian language» by Borys Hrinchenko – is an important example of Ukrainian language of the XIXth century, collected examples of oral territorial language of Ukraine of that time. This lexicographical work serves as a reliable and valuable source for diachronic research in sphere of dialect phrazeology. In the article the structure and semantics of prazeological units of dialect language on the material of «Vocabulary…» by B. Hrinchenko, which present different aspects of nation’s existence: person’s behavior, way of life, trades, ceremonies etc., are analyzed. Dialect phrazeological units, their components allow penetrating into dialectal system of the language, to determine borders of their functioning and their adoption in different groups of language speakers.